Elemental worlds: Specificities, exposures, alchemies. (December 2021) - Engelmann, Sasha; McCormack, Derek
The elements have become the focus of a significant volume of research by geographers and others. Engagements with the elements have been framed in terms of four elemental orientations: matter, molecule, milieu and media . Our aim is to consider what is at stake in efforts to think with, across and beyond these orientations. Avoiding any reduction of the elements to a single ontological or epistemological proposition, we explore possibilities for grasping their implication in the composition and decomposition of worlds. Doing this can be facilitated by thinking about these worlds in relation to three interrelated matters of concern: specificities, exposures and alchemies.